Statewide opioid prescriptions and the prevalence of adolescent opioid misuse in Ohio. (4th May 2017) - McKnight, Erin R.; Bonny, Andrea E.; Lange, Hannah L. H.; Kline, David M.; Abdel-Rasoul, Mahmoud; Gay, Joseph R.; Matson, Steven C.
ABSTRACT: Background : Little is known about the relationship between opioid prescribing practices and the prevalence of adolescent opioid misuse. Objective : To examine the relationships between both opioid prescriptions filled by adolescents and adults and adolescents seeking treatment for opioid misuse in Ohio. Methods : Analyses of large statewide databases from 2008 to 2012, including all 88 counties in Ohio. The Ohio Board of Pharmacy provided data regarding prescription opioids filled by adolescents (12–20 years, N = 50, 030, 820 doses) and adults (>20 years, N = 3, 811, 288, 395 doses) by county of residence. The Ohio Department of Mental Health and Drug Addiction Services provided annual treatment admissions for adolescent opioid misuse by county of residence ( N = 6446). Results : Adults filled prescriptions for nearly 100 oral opioid doses per capita annually, while adolescents filled prescriptions for approximately 7 oral opioid doses per capita annually. In Bayesian Poisson modeling examining the effect of annual adult per capita dose on adolescent treatment admissions, adjusted for annual adolescent per capita dose and year, an increase of one in the annual adult per capita opioid dose resulted in an increase of 1.3% (RR = 1.013, 95% HPD CI = [1.008, 1.017]) in the rate of adolescent treatment admissions. This association corresponds to a 99.99% chance that the adolescent treatment rate increases when the annual per capita adult dose is increased by one unit. Conclusion : The amount of opioids filled by adults in Ohio, although relatively stable from 2008 to 2012, is approximately 13 times that filled by adolescents and is significantly associated with adolescents seeking treatment for opioid misuse. Efforts to decrease adolescent opioid misuse should also focus on reducing adult opioid prescriptions.